RELEVANSI GAME-BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA: PERSEPSI MAHASISWA CALON GURU DI ERA DIGITAL - Triyulia, Ghea Nanda; Kintoko, Kintoko; Sulistyowati, Ani; Siswanto, Deny Hadi (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to describe the perceptions of Mathematics Education students at Universitas PGRI Yogyakarta (UPY) from the 2023 and 2024 cohorts, as pre-service teachers, regarding the relevance of Game-Based Learning (GBL) in enhancing students’ learning motivation in the digital era. The study employed a descriptive qualitative approach, with pre-service teacher students selected through purposive sampling as research subjects. Data were collected through in-depth interviews, observations, and documentation, and analyzed using interactive techniques consisting of data reduction, data display, and conclusion drawing. The findings indicate that the students possess a fairly good initial understanding and positive perceptions of GBL implementation. GBL is perceived as capable of fostering learning motivation, increasing perseverance, helping students cope with learning difficulties more adaptively, and aligning with the characteristics of 21st-century learning. However, the readiness of pre-service teachers to implement GBL still requires strengthening, particularly in pedagogical aspects and technical skills. This study underscores the importance of enhancing pre-service teacher competencies through training and practice-based experiences grounded in the TPACK framework to ensure that the implementation of Game-Based Learning can be effective and sustainable.